Distributed Control of Nonholonomic Robots Without Global Position Measurements Subject to Unknown Slippage Constraints - Zhang, Hao; Sun, Jianwen; Wang, Zhuping (IEEE/CAA journal of automatica sinica, 2022)
This paper studies the fully distributed formation control problem of multi-robot systems without global position measurements subject to unknown longitudinal slippage constraints. It is difficult for robots to obtain accurate and stable global position information in many cases, such as when indoors, tunnels and any other environments where GPS (global positioning system) is denied, thus it is meaningful to overcome the dependence on global position information. Additionally, unknown slippage, which is hard to avoid for wheeled robots due to the existence of ice, sand, or muddy roads, can not only affect the control performance of wheeled robot, but also limits the application scene of wheeled mobile robots. To solve both problems, a fully distributed finite time state observer which does not require any global position information is proposed, such that each follower robot can estimate the leader's states within finite time. The distributed adaptive controllers are further designed for each follower robot such that the desired formation can be achieved while overcoming the effect of unknown slippage. Finally, the effectiveness of the proposed observer and control laws are verified by simulation results.